An instance of ovarian calcification in the seabass, Lates calcarifer (Bloch) - Lal, Kuldeep K; Pandey, Ajay K (Indian Journal of Fisheries, 2011)
While studying the seasonal changes in the gonads of the female Latescalcarifer collected from Tambarparani estuary, Korampallan creek along theTuticorin coast (Gulf of Mannar), out of 311 fish samples examined, onespecimen weighing 8.50 kg and total length 925 mm, exhibited partial ovariancalcification. Histological examination of the calcified portion of ovary (afterpartial decalcification) revealed thickening of the ovigerous lamellae anddeposition of calcium in their lumina which were devoid of oocytes whereasthe non-clacified part of ovary possessed ova at chromatin nucleus andperinucleolar stage.